Adaptación, validez de constructo y confiabilidad de la escala de riesgo suicida Plutchik en adolescentes colombianos (2023)
Plutchik’s suicide risk scale has been widely used to assess suicide risk; however, studies on its psychometric properties in Colombian adolescents are unknown. The objective was to establish the adaptation, construct validity and reliability of the scale in Colombian adolescents in Colombian adolescents. An instrumental study was designed, in a sample made up of 481 adolescents with age between 13 and 20 years (M = 16.3, SD = 1.4), 46% corresponded to men. Exploratory Factor Analysis evaluated the construct validity and the number of factors was defined with the Horn Parallel Analysis and the adjustment with Confirmatory Factor Analysis. A reduced version of nine items was obtained grouped into two factors that explained 53% of the common variance and very good fit [ x2S-B = 26.36, gl = 26, p = 0.34; NNFI = 1.0, CFI = 1.0, RMSEA = 0.02, IC 90% (0.00, 0.05)]. The items discriminated between those who attempted suicide and those who had not tried. Cronbach’s alpha reliability for depression was .72 and .80 for suicidal risk, McDonald’s Omega was .82 and .94 respectively. It is concluded that the new reduced version of nine items of the Plutchik suicide risk scale has adequate psychometric characteristics and its use is recommended in the assessment of suicide risk in colombian adolescents. © 2019 Fundación Universitaria Konrad Lorenz.